Nanoparticles Filled Polymer Nanocomposites: A Technological Review. Issue 1 (1st January 2021) - Hiremath, Anupama; Murthy, Amar A; Thipperudrappa, Sridhar; K N, Bharath
Abstract: Incorporation of nanoparticles in polymeric matrices to develop polymer nanocomposite with an idea to maximize the "nano-effect" derived out of the nanoparticles and to minimize the disadvantages of the polymer is an emerging area of research. Nanoparticles in the form of nanosheets, nanotubes, nanofibrils and quantum dots are incorporated in polymers to fabricate polymer nanocomposites, which possess tunable mechanical, thermal, electrical, magnetic and optical properties. However, to realize a quality composite, it is imperative to ensure that the selected nanoparticles are uniformly distributed within the matrix and have good compatibility with the matrix material. Thus, one should ensure strict control over the selection and operating parameters of the fabrication method of polymer nanocomposites. The paper presents a review of various fabrication techniques employed to obtain nanoparticle-filled polymer nanocomposites. An effort is also made to understand the effect of such nanoparticles on the mechanical and thermal properties of polymer nanocomposites.